STUDENTS' SELF-DIRECTED LEARNING IN LISTENING CLASS - Melda Yeni (Fakultas Keguruan dan Ilmu Pendidikan, 2019)
the purpose of this research is to know the level of students’ self-directed learning at the second semester of English Study program of Islamic University of Indragiri. It is achieved by conducting a quantitative study. Questionnaire was distributed to 23 students to get the result of the research. The questionnaire was using Guttmann Scale. The result of this questionnaire revealed that students’ self-directed learning in listening class relies on low level.